A High-Order Iterate Method for Computing AT,S(2) - Xiaoji Liu; Zemeng Zuo (Journal of Applied Mathematics)
We investigate a new higher order iterative method for computing the generalized inverse AT,S(2) for a given matrix A. We also discuss how the new method could be applied for finding approximate inverses of nonsingular square matrices. Analysis of convergence is included to show that the proposed scheme has at least fifteenth-order convergence. Some tests are also presented to show the superiority of the new method.